Nanodelivery systems based on mucoadhesive polymer coated solid lipid nanoparticles to improve the oral intake of food curcumin. (June 2016) - Ramalingam, Prakash; Yoo, Sang Woo; Ko, Young Tag
Abstract: Although curcumin shows promising therapeutic efficacy, its food related and clinical application suffers from poor water solubility, stability and oral bioavailability. Chitosan coated solid lipid nanoparticles (NC)-based nanodelivery systems were developed in order to enhance the stability and oral bioavailability of curcumin and help incorporate it in functional foods and nutraceuticals. These NC nanoformulations were characterized by analyses of their mean particle size, zeta potential, encapsulation efficiency, drug loading capacity, crystallinity, stability, and in vivo studies. The NC showed prolonged physical stability at room and refrigerated temperature conditions. NC has been shown to increase the bioavailability of curcumin above that of curcumin suspensions after oral administration. Such nanoformulations will contribute to broadening the application of the bioactive curcumin in foods and nutraceuticals. Graphical abstract: Highlights: Food grade solid lipid nanoparticles (SLNs) were formulated and characterized. Chitosan was used to coat the surface of SLNs incorporated with curcumin. (NC) improved the stability of curcumin. NC improved the oral bioavailability of curcumin as compared to curcumin suspension.